Pertanyaan dan nasihat dokter untuk konsumsi sayur dan buah: penelitian potong lintang pada 10 puskesmas di Yogyakarta dan Sleman - Yayi Suryo Prabandari; Bagas Suryo Bintoro; Indira Utami Yusuf (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Mortality caused by noncommunicable disease (NCD) has increased in the last ten years in Indonesia in line with the elevation of NCD prevalence. The NCD mortality and prevalence can be prevented by practicing a healthy lifestyle. One of a healthy lifestyle is adequate vegetable and fruit consumption that unfortunately was still far from expectation in the Basic Health Survey 2007 and 2010. Puskesmas as primary health care should anticipate the problem by encouraging doctor to routinely ask and educate on a healthy lifestyle.Objective: This study aimed to assess physician ask and advice on vegetable and fruit consumption based on patient and physician report.Method: Two hundred and fifty-one patients from primary health care (Puskesmas) in Yogyakarta City and Sleman District participated in this cross-sectional survey. Subsequently, a survey of 57 physicians was conducted. Data were collected by structured questionnaires and exit interviews. We analyzed the data using Chi-Square test and logistic regression.Results: The results showed that patients have been asked and advice about vegetable and fruit consumption. However, the proportion of physician report was higher than the proportion of patient’s report. Patient who had gastrointestinal disorder, had body weight problem, suffered from diabetics and cardiovascular diseases were more being asked and educated about vegetable and fruit consumption than other symptoms or diseases. Patients who were female, not married and did not eat vegetable and fruit everyday reported more being asked and advised by doctor on fruit and vegetable consumption than patients who were male, married and did not regularly eat fruit and vegetable. There was no difference of patient’ s perception of the relation between their disease and fruit and vegetables consumption based on characteristics, symptoms, disease and the frequency of eating fruit and vegetable.Conclusion: Primary health care physician has asked and advised patient about vegetable and fruit consumption although did not routinely practice it. Delivering advice as part of patient education on high fiber diet should be included in the national insurance scheme, so that physician will routinely educate patient.